Land conflict hotspot in Chalinze District, Coast Region - Kalenzi, Deus (International Livestock Research Institute, 2018)
Map showing villages that had hot spot areas of conflict in 2018 in the district of Chalinze, Coastal (Pwani) region, Tanzania.